FREQUENCY OF INCIDENTAL PROSTATE CANCER IN PATIENTS PRESENTING WITH PALPABLE ENLARGED PROSTATE GLAND - Rasul, Ghulam; Khan, Ismail; Jan, Mir Alam; Ahmad, Tanveer; Khattak, Ikram Ullah; Aslam, Munir (Journal of Postgraduate Medical Institute, 2019)
Objective: To find out the frequency of incidental prostate cancer in patients presenting with palpable enlarged prostate gland. Methodology: This was a descriptive study conducted at Department of Urology, Lady Reading Hospital, Peshawar from January to December 2015. A total of 753 patients were observed and non-probability purposive sampling technique was used for sample collection. Patients with features of enlarged prostate i.e. bilateral symmetrical enlargement, palpable median sulcus and mobile rectal mucosa over the gland; PSA level of <10ng/ml and age >50 years were included. The chips of the resected prostate were collected in formalin and sent for histopathologist to detect the prostate cancer. All the quantitative and qualitative data were analyzed in SPSS version 22. Results: The mean age of the patients was 65 years ±12.713. Majority (60%) of the patients were in the age group of 56-60 years. Prostatism was the commonest presenting complaint (73%). Post voiding residual urine between 90 and 150 ml was found in 60% of patients. Incidental carcinoma of the prostate was found in 18 (2.3%) patients. Conclusions: Frequency of incidental carcinoma of prostate was 2.3% in patients with clinically palpable enlarged prostate gland.